Analysis of bacterial community structure in different types of Daqu based on third-generation sequencing and pure culture techniques - WANG Wenhang, CAI Wenchao, YU Peirong, CHEN Wei, SHAN Chunhui, GUO Zhuang, WANG Yurong (Zhongguo niangzao)
To investigate the differences in bacterial community structure between high- and medium-high-temperature Daqu, the bacterial community structure of the two types of Daqu was analyzed by third-generation sequencing technology, the correlation between bacterial community and gene functions of bacterial community were analyzed, and the strains were isolated and identified by microbial pure culture and molecular biology techniques. The results showed that the dominant bacterial phyla (average relative abundance>1%) in two types of Daqu included Firmicutes, and the dominant bacterial genera included Kroppenstedtia, and the dominant bacterial species included Kroppenstedtia eburnea. Principal coordinates analysis (PCoA) and linear discriminant analysis effect size (LEfSe) analysis results showed that there were significant differences in the bacterial community structure between the two types of Daqu, with Thermoactinomycetaceae and Dietziaceae as biomarkers for high- and medium-high-temperature Daqu, respectively. Correlation analysis results indicated that the bacterial community in medium-high-temperature Daqu exhibited higher stability. Functional prediction results showed that medium-high temperature Daqu had significantly higher average relative abundance in three functions: carbohydrate transport and metabolism, cell wall/membrane biosynthesis, and cellular motility and signal transduction mechanisms, compared to high- temperature Daqu. A total of 114 strains, belonging to 9 genera and 17 species, were isolated and identified from the two types of Daqu samples, mainly Bacillus licheniformis.